The social role of liturgy in the religion of the Qumran community - Arnold, Russell C. D. (Studies on the Texts of the Desert of Judah, 2006)
"This volume investigates the layers of meaning of the Qumran community's liturgical practice as prayer (communication with the divine), ritual (actions that establish and reinforce the social and ideological structures of the community), and speech (containing both verbal and non-verbal communication)."--Jacket.